Pengamatan Gejala Penyakit CVPD pada 12 Spesies Tanaman Jeruk - VEDERIS LEUNARDUS; I GEDE PUTU WIRAWAN; I KETUT SUADA; I GUSTI AYU DIAH YUNITI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Diseases Symptoms Observation at 12 Species of Citrus Plants This study was conducted to observe symptoms that showed by citrus plantswhich already tested by PCR carry CVPDr DNA Fragment. CVPDr is resistance geneto prevent plant from CVPD diseases. Based on observations in the field showed thatfive from twelve species showed the symptoms even already carry the gene. Five ofthem are Citrus reticulata Selayer Buleleng, Citrus nobilis Buleleng, Citrus nobilisPecatu, Citrus nobilis Tabanan, dan Citrus reticulata Keprok Gianyar. Mutationanalysis and homology analysis should be done after this observation to know whythis gene is not functional to prevent CVPD diseases.